KENDALA DALAM PENERAPAN DIVERSI TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA PENCURIAN (Studi di Polres Nias Selatan) - Kristiani Ndruru (Jurnal Panah Hukum, 2022)
Diversion is the transfer of case settlement from the criminal justice process to a process outside the criminal justice system. The crime of theft is a crime against the interests of individuals which is a crime against property or property. Children are part of the younger generation, both men and women who are not yet mature. The formulation of the problem in this study is how are the obstacles in the application of diversion to children as perpetrators of the crime of theft (Study at the South Nias Police Station). South Nias Police Station). The type of research used is a sociological legal research type with research specifications using descriptive research, the location of this research is the South Nias Police Station located in Telukdalam district, data collection techniques are through interviews, observations or observations, and document studies. Data analysis used qualitative analysis, namely by describing the data generated by outlining sentences that were arranged logically and systematically. Based on the results of research and discussion, it can be concluded that the obstacle in implementing diversion against children as perpetrators of the crime of theft (study at the South Nias Police Station) is the lack of ability and knowledge in giving approaches to litigants, both the victim's family and the perpetrator's family, so that no achievement is reached. diversion for the following reasons: Dissatisfaction of one of the litigants, because the victim feels aggrieved, the cost of compensation that the perpetrator cannot afford